The rights and obligations of a State under Article 3bis of the Chicago Convention pursuant to an intrusion of its sovereign air space by civilian aircraft (during peace times) - Hobe, Stephan (University of Pretoria, 2020)
Mini Dissertation (LLM)--University of Pretoria, 2019.